Endoscopic supracerebellar infratentorial approach to pineal and posterior third ventricle lesions in prone position with head extension: a technical note. (1st December 2020) - Spazzapan, Peter; Velnar, Tomaz; Bosnjak, Roman
ABSTRACT: Objective: The supracerebellar infratentorial (SCIT) approach is frequently used for the treatment of lesions in the pineal and posterior third ventricle region and can be performed in a sitting or prone position. We describe our experience with the purely endoscopic SCIT approach, using a prone position, with neck extension and head rotation. Methods: We analysed all paediatric and adult patients operated on between July 2013 and January 2018 using the purely endoscopic SCIT approach. The surgical procedure was conducted through a paramedian subtorcular key-hole suboccipital craniotomy. The assistant held the endoscope and the surgeon used fine, long shaft instruments for bimanual tumour dissection. The prone position with head retroflexion allowed a gravity-aided enlargement of the anatomical surgical corridor between tentorium and cerebellum and enhanced venous blood drainage, similarly to the sitting or semi-sitting position, but with a decreased risk of air embolism. Results: The approach allowed a complete removal of lesions located in the pineal region and in the posterior part of the third ventricle. Seven patients have been operated with this approach. All of them had the tumour completely removed. No permanent neurological deficits have been observed. Conclusions: The endoscopic SCIT approach enables effective and safe removal of pineal and posterior third ventricle lesions, even of moderate dimensions (up to 3 cm). The endoscope guarantees a detailed view and illumination of the deep-seated structures. The tumour resection can be performed with bimanual use of microsurgical instruments.